Local Government Policies in Learning Culture and Regional Language of Kaili in Palu City - Susanti, Ani; Waris, Irwan (Technium Social Sciences Journal, 2020)
This study aims to determine local government policies related to the development of learning culture and Kaili language for students. The Kaili tribe in Central Sulawesi is the majority of the largest ethnic groups. However, the development of the culture and language of the Kaili Regional Language (KRL) has undergone a significant downturn. Little research has been done to explore the preservation of culture and language that is driven through education. By using qualitative methods, the technique of determining informants using a purposive method is that people who are chosen to be informants are people who have in-depth knowledge of the problem under study. To strengthen the analysis, we used literature studies of PubMed, SCOPUS, ScienceDirect, Google Scholar, and personal journals. From the results of the research analysis, it was revealed that the Regional Government of Central Sulawesi, in this case the City of Palu, has issued a Regional Regulation in the form of the application of the Kaili language in the 2013 Curriculum in the arts and culture column and crafts for elementary school (ES) students. Meanwhile, for secondary schools and universities, it only takes the form of a communicative approach. However, this policy has not been running optimally. The use of Kaili Regional Language is still rarely seen being used during interactions in the school and college environment. So that in some areas, KRL is threatened with extinction.